Construction of a flocculent brewer's yeast strain secreting Aspergillus niger β-galactosidase - Domingues, Lucília (2000)
One way of improving heterologous protein production is to use high cell density systems, one of the most attractive being the flocculating yeast production system. Also, lactose is available in large amounts as a waste product from cheese production processes. The construction of flocculent and non-flocculent brewer's yeast strains secreting β-galactosidase and growing on lactose is presented. A plasmid was constructed coding for an extracellular β-galactosidase of Aspergillus niger and having, as selective marker, the yeast CUP1 gene conferring resistance to copper. This selective marker allows for the transformation of wild-type yeasts. This work represents an important step towards the study of heterologous protein secretion by flocculent cells.